Fighting the slave trade : West African strategies - Diouf, Sylviane A. (Sylviane Anna), 1952- (Western African studies., 2003)
Annotation While most studies of the slave trade focus on the volume of captives and on their ethnic origins, the question of how the Africans organized their familial and communal lives to resist and assail it has not received adequate attention. But our picture of the slave trade is incomplete without an examination of the ways in which men and women responded to the threat and reality of enslavement and deportation. Fighting the Slave Trade is the first book to explore in a systematic manner the strategies Africans used to protect and defend themselves and their communities from the onslaught of the Atlantic slave trade a nd how they assaulted it. It challenges widely held myths of African passivity and general complicity in the trade and shows that resistance to enslavement and to involvement in the slave trade was much more pervasive than has been acknowledged by the orthodox interpretation of historical literature. Focused on West Africa, the essays collected here examine in detail the defensive, protective, and offensive strategies of individuals, families, communities, and states. In ch apters discussing the manipulation of the environment, resettlement, the redemption of captives, the transformation of social relations, political centralization, marronage, violent assaults on ships and ports, shipboard revolts, and controlled participation in the slave trade as a way to procure the means to attack it, Fighting the Slave Trade presents a much more complete picture of the West African slave trade than has previously been available.